Should Corporate Social Responsibility Around The World be Mandatory or Voluntary? - Alwasmi, Mohammad; Alderbas, Ahmad (Comparative Law Review, 2021)
Corporate social responsibility (CSR) is an idea that has grown during the last three decades from the voluntary activity of business firms into a debate about whether CSR should be mandated by law because of the increased demand from society. Further, it has been argued that business corporations are owned by their shareholders, and the managers must concentrate on maximizing the wealth of their shareholders and not of the community. To determine how better to apply CSR, this paper begins with looking at the evolution of CSR as a system around the world and then discusses the definition of CSR. In addition, this paper explores the advantages and disadvantages of implementing voluntary CSR and then explores mandatory CSR. Moreover, in this paper, it is found that determining the proper CSR system depends on many factors in each country, such as the social, economic and legal factors that should be examined before applying mandatory or voluntary CSR.